Esophagojejunal Anastomosis Fistula, Distal Esophageal Stenosis, and Metalic Stent Migration after Total Gastrectomy. (6th April 2015) - Al Hajjar, Nadim; Popa, Calin; Al-Momani, Tareg; Margarit, Simona; Graur, Florin; Tantau, Marcel
Abstract : Esophagojejunal anastomosis fistula is the main complication after a total gastrectomy. To avoid a complex procedure on friable inflamed perianastomotic tissues, a coated self-expandable stent is mounted at the site of the anastomotic leak. A complication of stenting procedure is that it might lead to distal esophageal stenosis. However, another frequently encountered complication of stenting is stent migration, which is treated nonsurgically. When the migrated stent creates life threatening complications, surgical removal is indicated. We present a case of a 67-year-old male patient who was treated at our facility for a gastric adenocarcinoma which developed, postoperatively, an esophagojejunostomy fistula, a distal esophageal stenosis, and a metallic coated self-expandable stent migration. To our knowledge, this is the first reported case of an esophagojejunostomy fistula combined with a distal esophageal stenosis as well as with a metallic coated self-expandable stent migration.